2015
DOI: 10.12816/0028778
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Knowledge of Dental Surgeon about Halitosis from Two Dental Teaching Hospitals in Khartoum City

Abstract: The present study is a descriptive cross-sectional study that was conducted to assess the level of knowledge about halitosis among dental surgeons in Khartoum city. One hundred and six dental surgeons were randomly selected from two dental teaching hospitals: Khartoum Dental Teaching Hospital and Ribat Teaching Hospital in Khartoum city. A fully structured, close ended questionnaire was used. Data collected was assembled and analyzed using the SPSS statistical software. Most of the respondents were general pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In this study, the mean scores on knowledge of oral malodor in both dental students and young dentists' groups were not high. This result was similar to the previous studies had been done in dental professionals' knowledge on diagnosis and treatment of oral malodor knowledge in Sudan, Portugal, Nigeria and Netherlands [16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the mean scores on knowledge of oral malodor in both dental students and young dentists' groups were not high. This result was similar to the previous studies had been done in dental professionals' knowledge on diagnosis and treatment of oral malodor knowledge in Sudan, Portugal, Nigeria and Netherlands [16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…According to a previous study, one-fourth of the dental patients in Myanmar had oral malodor and 40% of dental patients are concerned about their breath odor [3]. Previous studies reported that sometimes dentists don't know clearly how to evaluate oral malodor problems [17,18]. It might be because of the lack of the modules related to oral malodor in detail at the undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most frequent reason of visiting a dentist following dental caries and periodontal diseases is halitosis. 3 Non-oral causes of halitosis are respiratory and gastrointestinal tract disturbances, metabolic disorders, systemic medications and carcinomas of aero digestive tract. 4 Anaerobic oral bacteria also play an important role in it as they survive and flourish in an oxygen deficient environment.…”
Section: Introductionmentioning
confidence: 99%